Analysis differences of VO2max between direct and indirect measurement in badminton, cycling and rowing - Rusdiana, A. (International Journal of Applied Exercise Physiology, 2020)
One of determinant factors of an athlete`s high achievement is a good physical condition. The cardiorespiratory endurance becomes one of the vital physical condition components in sport. The measurement of cardiorespiratory endurance for the aerobic capacity can be conducted by measuring the maximum oxygen consumption (VO2max). The measuring method of VO2max value can employ the direct and indirect measurement approaches. The purpose of this study was to analyze the VO2max through the direct and indirect measurement methods in badminton, rowing, and bicycle racing by considering the different mechanism of the dominant movement of each other. The method was a descriptive quantitative study with comparative approach. The sample of this study were West Java male athletes in rowing, badminton, and bicycle race involving 24 athletes. Each sport consisted of eight athletes as the samples. The anthropometrics profiles of the athletes include age 23.5 ± 2.6, height 174.8 ± 3.2, weight 63.4 ± 2.1 and body mass index 23.5 ± 3.7. According to the data analysis result of VO2max testing of badminton, rowing, and bicycle racing athletes, it concludes that there was a strong significant correlation in the measurement through direct and indirect measurement in badminton sport (r = 0.85), rowing sport (r = 0.82) and bicycle race (r = 0.78). The result of the correlation test result presents that theVO2max test conducted through direct and indirect measurement approach did not show a significant difference test result. Therefore, both parameters can be used in each of the sport.